Aluminium Nanoparticles: The Potentials of Metalized Explosives with Combined Destructive Effect (Combustion/Detonation). Issue 1 (December 2020) - Elbasuney, Sherif; Gaber Zaky, M.; Radwan, Mostafa; Maraden, Ahmed; Abdelkhalek, Sherif M.
Abstract: Even though, reactive metal particles can boost the energy density of explosive materials. Such particles will react behind the detonation wave front with decrease in detonation velocity and brisance (destructive effect). This study reports on the effective development of aluminium nanoparticles (NPS) of 100 nm particle size. Al NPs offered superior performance compared micron scale particles. Al NPs offered an increase in shock wave strength by 48 % compared with 17 % for micron scale particles. While micron-Al decreased the destructive effect of TNT by -6.5 %; Al NPs offered an increase in destructive effect by 21 %. The main outcome of this study is that Al NPs offered an enhanced detonation velocity of 6330 m/s compared with 5650 m/s for TNT. Additionally Al NPs offered decrease in TNT critical diameter from 40 mm to 20 mm. While conventional Al particles could act as desensitizer; Al NPs could act as sensitizer and could combust efficiently within detonation wave front. This study reports on the real development of metalized nano-composite explosives with combined destructive effect (combustion/detonation).